1975
DOI: 10.1098/rspa.1975.0167
|View full text |Cite
|
Sign up to set email alerts
|

Cascade damage effects on the swelling of irradiated materials

Abstract: The homogeneous rate theory of void growth is extended to include the possibility of forming vacancy loops when the irradiation produces cascade damage. The analysis provides a basis for understanding and correlating the relative swelling generated during electron; heavy ion and fast neutron irradiation. In order to illustrate the physical features of the model it is applied in some detail to calculating the volume swelling in solution treated M316 stainless steel for which there is a considerable amount of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(31 citation statements)
references
References 3 publications
1
29
0
1
Order By: Relevance
“…After that, they rapidly diffuse in metal B in the field of an external force, e.g., a pressure jump generated by an incidental collision during MA or by explosion at shockwave processing of metals. This mechanism is similar to the ballistic effects observed in reactor materials under radiation (Bullough et al, 1975;Murphy, 1987;Mansur, 1979) or at ion-beam processing of metals. However, molecular-dynamics simulation has revealed that for this mechanism to operate, local pressure at the phase boundary must be ~100 GPa (Gusak & Bushin, 1996), which is typical of explosion processing, whereas the mechanistic modeling of MA in ball mills has demonstrated that the maximal pressure during collisions is ~1 GPa (Maurice & Courtney, 1990;, i.e.…”
Section: Physical Background and Basic Assumptionssupporting
confidence: 70%
See 1 more Smart Citation
“…After that, they rapidly diffuse in metal B in the field of an external force, e.g., a pressure jump generated by an incidental collision during MA or by explosion at shockwave processing of metals. This mechanism is similar to the ballistic effects observed in reactor materials under radiation (Bullough et al, 1975;Murphy, 1987;Mansur, 1979) or at ion-beam processing of metals. However, molecular-dynamics simulation has revealed that for this mechanism to operate, local pressure at the phase boundary must be ~100 GPa (Gusak & Bushin, 1996), which is typical of explosion processing, whereas the mechanistic modeling of MA in ball mills has demonstrated that the maximal pressure during collisions is ~1 GPa (Maurice & Courtney, 1990;, i.e.…”
Section: Physical Background and Basic Assumptionssupporting
confidence: 70%
“…Relaxation of point defects towards equilibrium concentration during intervals between collisions occurs by two basic mechanisms: (i) interaction with edge components of dislocation loops, which act as volume-distributed sinks; in this case intersitials A i and B i become lattice atoms of the corresponding sort, and (ii) vacancyinterstitial annihilation, as a result of which an interstitial atom becomes a lattice one. To describe the rates of these processes we use certain results of the theory of defects in irradiated alloys (Bullough et al, 1975;Murphy, 1987;Mansur, 1979). The equilibrium concentration of self-interstitials in crystalline metals is typically assumed to be negligibly small.…”
Section: Derivation Of the Model Equationsmentioning
confidence: 99%
“…In the last one it is recognized that emitted small SIA clusters (SIA loops) make one dimensional motion and disappear at sinks such as dislocations and grain boundaries, resulting in the void swelling due to the so-called production bias [2][3][4] (an important bias in the matrix under irradiation together with the dislocation bias 1) ). SIA loops which make one dimensional motion are bundles of crowdions, that is, dislocation loops of the edge character with Burgers vector a=2h111i in bcc metals.…”
Section: Introductionmentioning
confidence: 99%
“…According to the BEK model, 28 the number of vacancies Q vl accumulated in the shrinking vacancy loops can be described in terms of the following mean-field kinetic equation:…”
Section: Kinetic Modelmentioning
confidence: 99%
“…27 The evolution of the interstitial cluster population should therefore be described in a way similar to the shrinking vacancy clusters. 6,[19][20][21][22][23][24][25] In other words, the Bullough-Eyre-Krishan ͑BEK͒ model, 28 originally developed for the vacancy clusters should also be applied to the interstitials clusters. 29 Interstitial clusters directly produced in cascades are generally smaller in size than their vacancy counterpart.…”
Section: Introductionmentioning
confidence: 99%